2018
DOI: 10.1080/09553002.2018.1492757
|View full text |Cite
|
Sign up to set email alerts
|

Radiosensitizer effect of usnic acid on Biomphalaria glabrata embryos

Abstract: The results presented here indicate that usnic acid makes cells more sensitive to the damaging effects of radiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Scientific research has driven the development of innovative alternatives, considering usnic acid as a source in obtaining new molecules, allowing structural modifications (syntheses) from usnic acid, whose purpose is to potentiate biological activity, leading to an optimization of therapeutic activity [ 24 , 25 ]. Our research group has expertise with relevant scientific productions with usnic acid [ 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ] and the production/synthesis of its derivative, potassium usnate [ 34 , 35 , 36 , 37 , 38 , 39 , 40 ]. This article aimed to describe the research found in the literature, the following databases were used: MEDLINE, Cochrane Central Register of Controlled Trials (CENTRAL/CCTR), Multidisciplinary Digital Publishing Institute (MDPI), Scientific Electronic Library Online (SciELO), Health of Latin America and the Caribbean Scientific Literature (LILACS), Google Scholar, and reference lists of relevant articles making an analogy of the molecule of usnic acid with potassium usnate, emphasizing the elucidation and structural characteristics, biological activities, bioavailability and toxicological aspects of both molecules and the advantages of using the promising hydrophilic derivative in different in vitro and in vivo assays when compared to usnic acid.…”
Section: Introductionmentioning
confidence: 99%
“…Scientific research has driven the development of innovative alternatives, considering usnic acid as a source in obtaining new molecules, allowing structural modifications (syntheses) from usnic acid, whose purpose is to potentiate biological activity, leading to an optimization of therapeutic activity [ 24 , 25 ]. Our research group has expertise with relevant scientific productions with usnic acid [ 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ] and the production/synthesis of its derivative, potassium usnate [ 34 , 35 , 36 , 37 , 38 , 39 , 40 ]. This article aimed to describe the research found in the literature, the following databases were used: MEDLINE, Cochrane Central Register of Controlled Trials (CENTRAL/CCTR), Multidisciplinary Digital Publishing Institute (MDPI), Scientific Electronic Library Online (SciELO), Health of Latin America and the Caribbean Scientific Literature (LILACS), Google Scholar, and reference lists of relevant articles making an analogy of the molecule of usnic acid with potassium usnate, emphasizing the elucidation and structural characteristics, biological activities, bioavailability and toxicological aspects of both molecules and the advantages of using the promising hydrophilic derivative in different in vitro and in vivo assays when compared to usnic acid.…”
Section: Introductionmentioning
confidence: 99%
“…Natural anticancer agents from plants such as Oroxylum indicum (OI) plant extract, curcumin, usnic acid, and Dictyota dichotoma brown alga extract are discovered to have radiosensitizing or radioprotective properties towards ionizing radiations. [24][25][26][27][28][29] Previously, Rahman et al have indicated that OI leaves extract could enhance the radiation dose of 6 MV and 10 MV photon beams on HeLa cancer cells. 30 The OI leaves extract provides a newly isolated baicalein-rich fraction (BRF) that has been validated to have anti-cancer, anti-virus and anti-oxidant properties.…”
Section: Introductionmentioning
confidence: 99%